Penguins - Thorburn, Nick 1981- (Fantagraphics Books, 2018)
"Told almost entirely without words, Penguins is one of the most playfully original graphic novels in recent memory. ... Relying on visual expression and the physical movement of his penguin characters, as well as the formal properties of sequential drawings (with penguins routinely moving within and without each page’s panel borders), Penguins is a series of interconnected short strips that, without words or human characters, does more to showcase the breadth of emotion we as humans experience than most prose novels."--Publisher's website
Keywords: Graphic novels; Penguins -- Comic books, strips, etc; Stories without words; Pinguine; Bildergeschichte; Comic